PENGARUH PENGGUNAAN METODE GALLERY WALK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SISTEM PEREDARAN DARAH KELAS VIII MTS MESRA PEMATANGSIANTAR TAHUN PELAJARAN 2019/2020 - Dwi Ayu Syah Putri, Nurhalima; Saragih, Marlindoaman (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2021)
This study aims to determine whether there is an effect on student learning outcomes using the Gallery Walk learning method on the circulatory system material for eighth graders at MTs Mesra Pematangsiantar in the 2019/2020 academic year. The sample taken in this study was Cluster Random Sampling, namely random sampling of classes. Therefore, classes VIII-2 and VIII-3 were selected, where class VIII-2 served as the experimental class 1 and class VIII-3 as the control class, with 32 students in each class. This research instrument used a pre-test and post-test in the form of options (a, b, c, d), each with 20 questions. Each correct question was given a score of 5 and each incorrect question was given a score of 0. The test technique was used to obtain data on Integrated Science learning outcomes. Based on the results of hypothesis testing using the t-test, the calculated t (2.227) > t table (2.000) at a significance level of α = 0.05 with degrees of freedom (df) = 32 + 32 - 2 = 62, so Ho is rejected and Ha is accepted, meaning there is an effect on student learning outcomes using the Gallery Walk method on the circulatory system material for class VIII MTs Mesra Pematangsiantar in the 2019/2020 Academic Year.